USE OF LITERATURE IN THE SECOND LANGUAGE CLASSROOM - Abeysooriya, B.K.P (A thesis submitted for the Degree of Master of Arts, 1992)
This d i s s e r t a t i o n i s based on a p r o j e ct c a r r i e d out to e x p l o r e the p o s s i b i l i t i e s of i n t r o d u c i n g l i t e r a t u r e i n the language classroom. In order to i n t r o d u c e l i t e r a t u r e to language l e a r n e r s s e l e c t e d f o r u n i v e r s i t y admission, a sample of prose e x t r a c t s was s e l e c t e d from the works of n a t i v e as w e l l as non-native w r i t e r s and was used w i t h a sample p o p u l a t i o n . Neither poetry nor drama was used i n t h i s p r o j e c t as i t was the f i r s t step i n i n t r o d u c i n g l i t e r a t u r e f o r the students who p a r t i c i p a t e d i n i t . The main aims of t h i s p r o j e c t were to enable students improve t h e i r r e a d i n g by exposing them to whole t e x t s and to p r o v i d e them w i t h o p p o r t u n i t i es to respond to l i t e r a r y elements such as c h a r a c t e r i z a t i o n , c r e a t i o n of atmosphere, and suspense. It a l s o aimed at d e v e l o p i n g students' c r i t i c a l and imaginative powers through i n t e r a c t in w i t h l i t e r a r y t e x t s as w e l l as i n c r e a t i n g an i n t e r e s t i n students to read l i t e r a t u r e , which i s a r i c h source of p l e a s u r e and enjoyment.